Simulation Models of the Seawater Greenhouse - M. Al-Ismaili, Abdulrahim; Bait Suwailam, Tahani (International Journal of Engineering and Technology, 2018)
In arid climates, extremely high temperatures in the summer and the chronic water scarcity put a firm barrier against agricultural development and sustainability. The SWGH technology is an engineering phenomenon that came to overcome both the constraints particularly in areas where seawater is accessible and/or brackish groundwater is available. It is a greenhouse used to cultivate crops and at the same time produce its own freshwater need. This study aimed to highlight the models that were carried out to simulate the SWGH as a whole or only the dehumidification rate of the SWGH condenser. Four types of simulation models were identified, namely, analytical, numerical, empirical and artificial neural network simulations. The factors affecting the dehumidification rate were also discussed taking into consideration the results from the simulation models.Â Â